1998
DOI: 10.1095/biolreprod59.2.371
|View full text |Cite
|
Sign up to set email alerts
|

Local Regulation of Macrophage Subsets in the Adult Rat Testis: Examination of the Roles of the Seminiferous Tubules, Testosterone, and Macrophage-Migration Inhibitory Factor1

Abstract: In the adult rat testis, macrophages belong to one of two subsets differentiated by expression or lack of expression of the resident macrophage surface antigen recognized by monoclonal antibody ED2. Local regulation of the testicular macrophage subsets was investigated in normal and 4-wk experimentally cryptorchid adult rats with and without s.c. testosterone implants (T-implants). Macrophage subsets ED2(+) (resident-type) and ED2(-) (monocyte-like) were identified immunohistochemically and counted in perfusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 48 publications
1
52
0
1
Order By: Relevance
“…In our study, the administration of T3 implant as expected resulted in the reduction of serum gonadotropin levels below those necessary to sustain spermatogenesis. In contrast, the higher-dose T24 implants cause supraphysiological serum concentrations and resulted in sufficient levels (10-40% of normal testicular levels) to support qualitatively normal seminiferous tubule function (40,45,46). The histological assessment of the treated animals clearly showed that testosterone replacement provided a significant degree of protection against the development of orchitis with only 17% of EAO+T3 and 33% of EAO+ T24 animals developing the disease, compared with 80% when no hormone intervention was performed.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, the administration of T3 implant as expected resulted in the reduction of serum gonadotropin levels below those necessary to sustain spermatogenesis. In contrast, the higher-dose T24 implants cause supraphysiological serum concentrations and resulted in sufficient levels (10-40% of normal testicular levels) to support qualitatively normal seminiferous tubule function (40,45,46). The histological assessment of the treated animals clearly showed that testosterone replacement provided a significant degree of protection against the development of orchitis with only 17% of EAO+T3 and 33% of EAO+ T24 animals developing the disease, compared with 80% when no hormone intervention was performed.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, mammalian testicular macrophages display a novel cytokine secretion profile compared with peritoneal macrophages [24] and retain their cytotoxic and phagocytic capacities, although they have greatly diminished proinflammatory functions and exhibit immunosuppressive activity [25]. Moreover, the recruitment and maintenance of the resident macrophages are clearly under the control of testicular soluble factors [26], such as macrophage migration inhibitory factor [27] and monocyte chemoattractant protein-1 [28,29]. The testicular sbNLCs are also recruited by testicular soluble factors, show a different cytokine production profile [8], and retain some phagocytic and ROI production capabilities, although they are impaired severely by the testicular microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Testicular IF was assayed for testosterone without extraction using a direct 125 I-testosterone radioimmunoassay (44).…”
Section: Testosterone Assaymentioning
confidence: 99%